2018
DOI: 10.1186/s40795-018-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant mothers have limited knowledge and poor dietary diversity practices, but favorable attitude towards nutritional recommendations in rural Ethiopia: evidence from community-based study

Abstract: Background: Mothers' nutrition is crucial for good pregnancy outcomes and in improving children's nutritional status. The present study aimed to examine the level of knowledge and attitude towards maternal nutrition and dietary diversity practices among pregnant mothers in rural central Ethiopia. Methods: In-depth analysis of data from a prospective study involving a total of 389 eligible pregnant women, enrolled during their second antenatal care (ANC) visit was conducted between August 2014 and March 2015. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
2
34
0
5
Order By: Relevance
“…Many women in sub-Saharan Africa including Ethiopia remain particularly exposed to inadequate intake of micronutrients, resulting in different types of malnutrition and its complications. Seven percent of the global disease burden and at least one-fifth of maternal deaths and poor maternal outcomes are as the result of maternal inadequate dietary diversity [10,11]. About one million neonates die on the first day and in the first week of life due to inadequate dietary intake of the mothers prior to and during pregnancy, as linked with increasing trends in maternal anemia, mortality, and adverse birth outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many women in sub-Saharan Africa including Ethiopia remain particularly exposed to inadequate intake of micronutrients, resulting in different types of malnutrition and its complications. Seven percent of the global disease burden and at least one-fifth of maternal deaths and poor maternal outcomes are as the result of maternal inadequate dietary diversity [10,11]. About one million neonates die on the first day and in the first week of life due to inadequate dietary intake of the mothers prior to and during pregnancy, as linked with increasing trends in maternal anemia, mortality, and adverse birth outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its serious consequences on birth weight and other birth outcomes, nutrient intakes of Ethiopian pregnant women were less than the recommended amounts for several key nutrients [24,25]. This is hypothesized to be due to poor dietary habits of pregnant women since the majority of pregnant women in the country take a cereal-based monotonous diet low in nutrient content and with poor bioavailability [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…8 The majority of participants in our study also identified the components of a balanced diet and reported the causes of undernutrition. In contrast, a study in Ethiopia found that, only half of the pregnant women reported adequate knowledge about a balanced diet 22 and a study in Lebanon indicated that 65% of women did not know the causes of undernutrition. 9 The findings of the current study may demonstrate some previous exposure to certain dietary-related topics among pregnant women, either at home or in the antenatal care setting.…”
Section: Discussionmentioning
confidence: 91%